Individual Treatment Decisions for Central Neurocytoma - Han, Song; Yang, Zuocheng; Yang, Yakun; Qi, Xueling; Yan, Changxiang; Yu, Chunjiang (Frontiers in Neurology, 2020)
Objective: Central neurocytomas (CNs) are rare, and this has resulted in a paucity of information and a lack of clarity regarding their optimal management. This study aimed to explore individual treatment strategies for CNs and the benefits of these strategies for patients. Methods: This single-center study retrospectively analyzed data from 67 patients with CNs who underwent surgery. Based on the extent of resection, patients were divided into complete and incomplete resection groups. The patients were followed, and overall survival (OS) and progression-free survival (PFS) were determined. Results: Of 62 patients (77.03%) who underwent complete resections, 24 received radiotherapy (43.64%). Of 12 patients who underwent incomplete resections, 9 (75.00%) received radiotherapy. The OS (p = 0.003) and PFS (p = 0.006) intervals were significantly longer in the complete resection group than in the incomplete resection group. Postoperative radiotherapy did not affect OS (p = 0.129) or PFS (p = 0.233) in the complete resection group. In the incomplete resection group, postoperative adjuvant radiotherapy prolonged patient survival significantly (p = 0.021). PFS was significantly longer among patients who underwent complete resection without radiotherapy than in those who underwent incomplete resection followed by radiotherapy (p = 0.034). Functional dependence on admission, which was defined as a Karnofsky Performance Status score < 70, was an independent risk factor associated with mortality and long-term survival in patients with CN. Postoperative complications were not associated with the amount of tumor resected. The prognosis of patients aged ≥ 50 years was relatively poor. The atypical CN recurrence rate was relatively high (7.84%). Conclusions: To protect function as much as possible, complete tumor resection should be the first choice of treatment for CN. After gross total resection, adjuvant radiotherapy is not acceptable. Postoperative adjuvant radiotherapy improves the prognosis of patients who have undergone incomplete tumor resections. Adjuvant radiotherapy is not recommended after complete resections of atypical CNs, and close follow-up with imaging is required. Our findings can help guide decision- making regarding the treatment of CNs and could potentially maximize the benefits of treatment for patients with CN.